Efektivitas Metode Modelling Terhadap Keterampilan Memasang Baju Berkancing Bagi Anak Tunagrahita Kategori Sedang di SLB Muhammadiyah Pauh IX Padang - Putri, Cece Kurnia; Kasiyati, Kasiyati (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2024)
This  Research is motivated by the low ability of self-development in mentally retarded children in the moderate category, especially self-development in putting on button-up clothes that researchers found at SLB Muhammadiyah Pauh IX Padang. Based on the results of the assessment that had been done, the child only got a score of 8%. The purpose of this study was to prove whether the modeling method was effective in improving the button-up shirt-fitting skills of medium category mentally retarded children type. This research is an experimental research with single subject research (SSR). Using A-B-A design with a single subject and data analysis using Visual Graphic analysis techniques. The results of the research on the skill of putting on button-down shirts were carried out continuously for 18 meetings with the results in the baseline condition (A1), namely 23%, while in the Intervention condition (B) it was 81%, and in the baseline A2 condition the children obtained a stable score of 85%. so that there was an increase in the skills of wearing button-down shirts for class C students at SLB Muhammadiyah Pauh IX Padang by using the modeling method. Based on the results above, it can be concluded that the skill of putting button-down clothes increases by using the modeling method in the moderate category of mentally retarded children.